2020
DOI: 10.1117/1.jrs.14.044503
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of InSAR tropospheric signal correction methods

Abstract: Tropospheric signals are considered as one of the most important performance limitations to compute the deformations caused by earthquake, subsidence, volcano, and so on using interferometric synthetic aperture radar (InSAR) technique. Various correction methods have been proposed to reduce the effect of these signals in displacement fields in previous research works. Different types of correction methods are used to estimate the tropospheric signal on InSAR observations. For this purpose, meteorological data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although we attempt to correct for signals caused by tropospheric delays, no currently available method can remove all of this noise, especially delays arising from the turbulent component of the atmosphere [42][43][44]. Previous studies have shown that in general, weather-model derived corrections can reduce the noise by 2-16% [45] resulting in an RMSE of around 2-3 cm [42] in individual interferograms.…”
Section: Discussionmentioning
confidence: 99%
“…Although we attempt to correct for signals caused by tropospheric delays, no currently available method can remove all of this noise, especially delays arising from the turbulent component of the atmosphere [42][43][44]. Previous studies have shown that in general, weather-model derived corrections can reduce the noise by 2-16% [45] resulting in an RMSE of around 2-3 cm [42] in individual interferograms.…”
Section: Discussionmentioning
confidence: 99%
“…In the first step of processing, the subsidence points need to be carefully identified. Given that the weather conditions of the study area may result in a change in the subsidence signal position obtained from InSAR, a precise method should be used to eliminate the tropospheric effect in radar results and to obtain an accurate diagnosis of signals [14,15]. In the following, a detailed method to correct the tropospheric effect of InSAR measurements is described.…”
Section: Background and Methodologymentioning
confidence: 99%
“…As to Pan'an New City, the correlation is always higher in urban areas. The latter relates to the interaction between radar waves and the atmosphere including ionospheric [27], tropospheric [28][29][30][31], etc. Even though there are ways to make them weaker, it is hard to eliminate them.…”
Section: Technical Principle Of Sbas-insarmentioning
confidence: 99%